PERANAN KOMUNIKASI ANTARPRIBADI TERHADAP HUBUNGAN MASYARAKAT IKECAMATAN TAMALATE KELURAHAN MANGASA KOTA MAKASSAR - Fyan Andinasari Kuen; Afrizal . (Jurnal Ilmiah Pranata Edu, 2019)
ABSTRAKThis study discusses interpersonal communication on community relations in the mangasa village, the role of interpersonal communication on inter-community relations in the District of Tamalate, Kelurahan, Mangasa, Makassar City. This study uses a survey approach using quantitative descriptive analysis with reference to data collection in field research, interview questionnaires and also supported by secondary data. The results obtained from this study, namely interpersonal communication on community relations in the village, overall are considered good. This is indicated by the results of observations that show the majority of respondents, namely as many as 75% still respect each other and uphold the martyrs and their respective cultures. Of the many residents of the village of Mangasa there are some people who lack the awareness to communicate interpersonal among neighbors / around the house so that it can create a sense of uncertainty or mutual suspicion if there is no openness. Keyword : interpersonal communication, community relations